Comparative evaluation of antibacterial property of bioactive glass alone and its combination with chlorhexidine against Enterococcus faecalis - An In vitro study - S Soumya; M A Faisal Gaffoor; Anoop Samuel; Rethi Gopakumar; C Sabari Girish; N C Sajeena (Wolters Kluwer Medknow Publications, 2021)
Context: One of the most common organisms responsible for root canal failure even after the usage of intracanal medicament is Enterococcus faecalis. Newer medicaments with higher antibacterial efficacy against E. faecalis need to be analyzed. Aim: The aim of this study was to compare the antibacterial property of bioactive glass (BAG) alone and its combination with chlorhexidine (CHX) against E. faecalis. Materials and Methods: Eighty permanent maxillary single-rooted teeth were included in the study. These teeth were randomly divided into three groups of ten teeth each. Dentin blocks were prepared. After debris and smear layer removal, dentin blocks were inoculated with E. faecalis and incubated for 7 days for biofilm formation. Medications including BAG alone and combination of CHX with BAG were placed into the dentin blocks and incubated at 37°C for 72 h. Dentinal shavings were collected, and the mean bacterial count was recorded. Statistical Analysis: The comparison of colony-forming unit (CFU) counts was done using one-way analysis of variance, Tukey's post hoc test, and unpaired t-test. The analysis was done using the Statistical Package for the Social Sciences version 20.0 for Windows. Results: Based on the CFU count obtained after 72 h, compared to the control group, both Group 1 and Group 2 reduced the bacterial load effectively. In comparison with Group 1, Group 2 (combination) was found to be more effective against E. faecalis. Conclusion: It can be concluded that although BAG was effective against E. faecalis, its efficacy increased significantly in combination with CHX.